Spatial Transcriptome and Single Nucleus Transcriptome Sequencing Reveals Tetrahydroxy Stilbene Glucoside Promotes Ovarian Organoids Development Through the Vegfa‐Ephb2 Pair - Chunlan Mu; Xiaoyong Li; Jiamei Yang; Geng G. Tian; Hepeng Bai; Wenhui Lin; Linhui Wang; Ji Wu (Advanced Science)
Abstract Ovarian dysfunction is a major factor leading to female infertility. Understanding how to improve or reshape ovarian function has become an important entry point for preventing and treating female infertility caused by ovarian dysfunction. Here, plant‐derived compounds are screened for in vitro activity upon ovarian organoids derived from feeder‐free female germline stem cells. Tetrahydroxy stilbene glucoside (TSG) is found to promote the development of ovarian organoids. Single nucleus transcriptome sequencing and spatial transcriptome sequencing are used to establish a comprehensive spatiotemporal map to elucidate the role of TSG in ovarian organoid development, encompassing cell types and subtypes, transcription factors, pseudo‐time sequence, and cell communication dynamics. This analysis indicates that TSG promotes ovarian organoid development through the vascular endothelial growth factor A‐Eph receptor B2 ligand‐receptor pair between granulosa cells and oocytes. This study has enhanced the understanding of the mechanisms of ovarian organoid development, establishes a technical platform for screening compounds for treating infertility and related diseases, and lays a foundation for clinically applying plant‐derived compounds.